PENGARUH COUNTRY OF ORIGIN DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SERUM SOMETHINC PADA MAHASISWA UNIVERSITAS DIPONEGORO - Apriatni Endang Prihatini; Sudharto Prawata Hadi; Yesserine Girlen Dashinta (Jurnal Ilmu Administrasi Bisnis, 2025)
Somethinc is one of Indonesian’s serum brand. There has been a decline in the ranking of the Top 10 Best-Selling Serum Brands in terms of sales volume. Sales volume percentage of Somethinc’s serum has increase but its ranking dropped to second place. This study aims to determine the influence of Country of origin and Electronic word of mouth on the purchasing decision of Somethinc serum products used explanatory research with a quantitative approach.. The sampling technique used is non-probability sampling. The number of respondents obtained was 100 students from Diponegoro University who use Somethinc serum products and have seen reviews of Somethinc serum on social media, which were then analyzed using SPSS 22.0. The results of the analysis indicate that there is an influence of Country of origin on Purchasing Decision. Electronic word of mouth also has an influence on the Purchasing Decision and Country of origin and Eletronic Word of Mouth have an influence on the Purchasing Decision of Somethinc serum products.